Clearwater Meeting - Krope, Linda (Environmental Defense Center)
E-mail message from Linda Krop, Chief Counsel of the Environmental Defense Center, to various people, including Lupe Anguiano, to organize a meeting concerning Clearwater Port LNG proposal.